Speciation and long- and short-term molecular-level dynamics of soil organic sulfur studied by X-ray absorption near-edge structure spectroscopy - Solomon, D.; Lehmann J; Knoth de Zarruk, K.; Dathe, J.; Kinyangi, James; Liang B; Machado S (Wiley, 2011)
We investigated speciation, oxidative state changes, and long- and short-term molecular-level dynamics of organic S after 365 d of aerobic incubation with and without the addition of sugarcane residue using XANES spectroscopy. Soil samples were collected from the upper 15 cm of undisturbed grasslands since 1880, from undisturbed grasslands since 1931, and from cultivated fields since 1880 in the western United States. We found three distinct groups of organosulfur compounds in these grassland-derived soils: (i) strongly reduced (S0 to S1+) organic S that encompasses thiols, monosulfides, disulfides, polysulfides, and thiophenes; (ii) organic S in intermediate oxidation (S2+ to S5+) states, which include sulfoxides and sulfonates; and (iii) strongly oxidized (S6+) organic S, which comprises ester SO4 S. The first two groups represent S directly linked to C and accounted for 80% of the total organic S detected by XANES from the undisturbed soils. Aerobic incubation without the addition of sugarcane residue led to a 21% decline in organanosulfur compounds directly linked to C and to up to an 82% increase inorganic S directly bonded to O. Among the C-bonded S compounds, low-valence thiols, sulfides, thiophenic S, and intermediate-valence sulfoxide S seem to be highly susceptible to microbial attack and may represent the most reactive components of organic S pool in these grassland soils. Sulfonate S exhibited a much lower short-term reactivity. The incorporation of sugarcane residue resulted in an increase in organosulfur compounds directly bonded to C at the early stage of incubation. However, similar to soils incubated without residue addition, the proportion of organic S directly linked to C continued to decline with increasing duration of aerobic incubation, whereas the proportion of organic S directly bonded to O showed a steady rise.